From the Manifesto to the Internet: Relations between Written Text, Literature, Performance Art in Latin America - Arenas, Rodrigo (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This work addresses the dialogue between written text and performance art, based on the praxis of the latter, focusing on the ways in which performance art is nourished by the written text. The written text is analyzed as an element in the construction of performance pieces; as a record; as a paratext; as a mean to discuss performance art; from the peculiarities of the relationship between literary and performance text, and the possibilities that emerge under the new technologies. An exploratory methodology is used, taking into account the author’s experiences in the area, and assuming a Latin American perspective, by which we try to contribute to the construction of a theoretical body from and towards our territories